2016
DOI: 10.1016/j.apjtm.2016.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of miR-467b on atherosclerosis of rats

Abstract: miR-467b can alleviate the AS lesions of ApoE(-/-) rats, and its inhibiting effect on AS may be related to LPL expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Previous studies demonstrated the involvement of miR-467b in cholesterol ester formation, atherosclerosis and hepatic steatosis (Ahn et al, 2011;Guan et al, 2016;Wang et al, 2017). The regulatory effect of miR-467b on pro-inflammatory cytokines inspired us to explore its role in OA progression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated the involvement of miR-467b in cholesterol ester formation, atherosclerosis and hepatic steatosis (Ahn et al, 2011;Guan et al, 2016;Wang et al, 2017). The regulatory effect of miR-467b on pro-inflammatory cytokines inspired us to explore its role in OA progression.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that miR‐467a‐5p is rapidly up‐regulated by high glucose in vitro and in vivo and regulates angiogenesis by targeting Thbs1 mRNA 21‐24 . Others report this miRNA prevents vascular inflammation by targeting lipoprotein lipase in macrophages 21,22,25‐28 . Yet, the physiological function of miR‐467a‐5p and the physiological significance of its rapid up‐regulation by hyperglycaemia remained unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] Others report this miRNA prevents vascular inflammation by targeting lipoprotein lipase in macrophages. 21,22,[25][26][27][28] Yet, the physiological function of miR-467a-5p and the physiological significance of its rapid up-regulation by hyperglycaemia remained unknown.…”
mentioning
confidence: 99%
“…Thus, miR‐27 (with many target genes) can be a potential biomarker in the diagnosis and treatment of atherosclerosis and its complications. Moreover, overexpression of miR‐188 and miR‐467b can reduce lipid accumulation and inflammatory cytokine secretion by targeting TLR4 and LPL expression levels, respectively, in ApoE − / − mice and may be a potential approach for treating atherosclerosis . In addition, miR‐30c affects lipid metabolism so that its overexpression decreases lipid synthesis pathways and lipoprotein secretion .…”
Section: Preclinical Studies Of Mirnas In Atherosclerosismentioning
confidence: 99%